Development of Flipbook-Based Thematic Learning to Improve Elementary School Students Learning Outcomes - Dzakiyah, Muniroh; Shidiq, Galih Albarra; Permana, Roni (DAS Institute, 2023)
Education is a means to lead to the growth and development of the nation. Flipbook-based thematic learning is an effort made so that students can improve learning outcomes. This study aims to examine and explore the application of flipbook teaching materials in thematic learning to improve learning outcomes. The method used in this research is a systematic literature study and in accordance with the discussion, namely thematic learning, flipbooks, and learning outcomes. Based on the results of a systematic review of the literature, flipbook-based thematic learning can be used as an alternative by teachers to improve student learning outcomes. However, the findings indicated that flipbook-based thematic learning can improve learning outcomes of elementary students through a positive impact on thematic learning in the elementary school students. Therefore, it is important to explore more detail on the efficient in delivering material and easy to understand and increase student interest in thematic learning.